Composite limestone powder concrete and preparation method thereof

By using composite limestone powder formula in concrete, combined with specific raw materials and preparation processes, the shortcomings of traditional concrete in terms of mechanics, durability and waterproof performance are solved, and better performance is achieved.

CN119874287APending Publication Date: 2025-04-25ZHEJIANG LONGYOU TONGQU BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510054904.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional concrete has shortcomings in terms of mechanical properties, durability and waterproofing properties, and it is difficult to meet complex and diverse engineering needs.

Method used

A composite limestone powder concrete, which is formulated with silicate cement, limestone powder, fly ash, steel fibers, hollow glass microbeads, waterproofing agents and functional additives, is used to prepare concrete with excellent properties through a specific stirring and curing process.

Benefits of technology

The composite limestone powder concrete not only improves mechanical properties and durability, but also significantly improves waterproof performance, thereby extending the service life of the concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241113870000101
    Figure BDA0005241113870000101
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to composite limestone powder concrete and a preparation method thereof. The concrete is prepared from the following raw materials in parts by weight: 320 to 380 parts of Portland cement, 1000 to 1200 parts of coarse aggregate, 750 to 850 parts of fine aggregate, 80 to 110 parts of limestone powder, 60 to 100 parts of fly ash, 30 to 50 parts of steel fiber, 20 to 30 parts of hollow glass beads, 10 to 15 parts of waterproof agent, 6 to 10 parts of functional additive and 200 to 220 parts of water, the coarse aggregate is selected from limestone macadam with the compressive strength of more than 90 MPa, the acicular content of less than 5%, the silt content of less than 1% and the particle size of 5-25 mm; the prepared composite limestone powder concrete not only has excellent mechanical properties and durability, but also has excellent waterproof performance, and the service life of the concrete is prolonged to a certain extent while the quality of the concrete is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a composite limestone powder concrete and a preparation method thereof. Background Art

[0002] With the rapid development of the construction industry, concrete, as one of the most commonly used building materials, has always been the focus of research on the optimization of its performance. Traditional concrete has certain limitations in some aspects, such as the need to improve working performance, unsatisfactory strength development, or insufficient durability. Due to its wide source and relatively low cost, limestone powder has gradually been tried to be used in concrete as a mineral admixture to improve some of the properties of concrete, but the addition of a single limestone powder often cannot fully meet the complex and diverse engineering needs. In actual engineering applications, there is an urgent need for a composite limestone powder concrete that can comprehensively improve various performance aspects to adapt to construction projects with different environments and load-bearing requirements.

[0003] A green concrete with a high limestone powder content is disclosed in the patent document with application number "CN201810040707.3", which belongs to the field of green concrete technology and includes the following components in parts by weight: 300-350 parts of Portland cement, 100-130 parts of modified limestone powder, 20-40 parts of modified ultrafine fly ash, 400-500 parts of river sand, 300-400 parts of machine-made sand, 900-1000 parts of crushed stone, 160-165 parts of water, and 6-6.5 parts of water reducer. Although the concrete provided in this patent document has excellent antifreeze performance, its own waterproof performance and mechanical properties are relatively insufficient, which not only affects the quality of the concrete, but also shortens its service life to a certain extent. Therefore, the present invention provides a composite limestone powder concrete and a preparation method thereof to solve the above-mentioned technical problems. Summary of the invention

[0004] The purpose of the present invention is to provide a composite limestone powder concrete and a preparation method thereof. The concrete prepared by the present invention not only has excellent mechanical properties and durability, but also has excellent waterproof performance, which ensures the quality of the concrete and also prolongs its service life to a certain extent.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A composite limestone powder concrete is composed of the following raw materials in parts by weight: 320-380 parts of silicate cement, 1000-1200 parts of coarse aggregate, 750-850 parts of fine aggregate, 80-110 parts of limestone powder, 60-100 parts of fly ash, 30-50 parts of steel fiber, 20-30 parts of hollow glass microspheres, 10-15 parts of waterproofing agent, 6-10 parts of functional additives and 200-220 parts of water.

[0007] Furthermore, the water content of the limestone powder is less than 1.0wt%, and the specific surface area is 600-750m 2 / kg, 45μm sieve residue is less than 15wt%, average particle size is 7.5-8.0μm, and calcium carbonate content is greater than 75wt%.

[0008] Furthermore, the coarse aggregate is limestone crushed stone with a compressive strength greater than 90 MPa, a needle-like content less than 5%, a mud content less than 1%, and a particle size of 5 to 25 mm.

[0009] Furthermore, the fine aggregate is selected from zone II medium sand, whose apparent density is 2650-2670 kg / m 3 The particle diameter is 0.25-0.5 mm and the mud content is less than 1.0%.

[0010] Furthermore, the bulk density of the hollow glass microspheres is greater than 700 kg / m 3 , the silicon dioxide content is greater than 50%, and the aluminum oxide content is greater than 20%.

[0011] Furthermore, the silicate cement is selected from P.O42.5 grade ordinary silicate cement; the fly ash is selected from F class II fly ash.

[0012] Furthermore, the preparation method of the waterproofing agent is as follows: methyl methacrylate, epoxy resin and triacetin are put into a reaction device at a mass ratio of 1:1.5-2.5:1-2, and mixed and stirred at a rate of 300-500r / min for 10-20min; then the obtained mixture is heated to 70-80°C, kept warm and stirred for 2-3h, and then 0.8-1.0 times the mass of octadecanoic acid and 1-1.5 times the mass of benzoic acid are added, and after stirring evenly, the reaction is continued at a temperature of 70-80°C and kept warm and stirred for 2-3h; after the reaction is completed, the resultant components are naturally cooled to room temperature to obtain the waterproofing agent.

[0013] Furthermore, the preparation method of the functional additive comprises the following steps: putting 2-methacrylamide, maltose and water into a reaction kettle at a mass ratio of 1:0.8-1.2:3-5, adding 4-tert-butyl-1,2-dihydroxybenzene and 20-40% trihydroxyethylamine in an amount of 0.2-0.5% by mass of 2-methacrylamide and stirring well, mixing and stirring evenly, and then keeping warm for reaction at a temperature of 50-80°C for 3-5h; after the reaction is completed, mixing and stirring the resultant components with 3-4 times by mass of methacrylic acid, 10-15 times by mass of methoxy polyethylene glycol monomethacrylate, and 0.02-0.04 times by mass of a reaction accelerator, and keeping warm for reaction at a temperature of 65-75°C for 2-5h; after the reaction is completed, the functional additive is obtained.

[0014] Furthermore, the reaction accelerator is selected from any one of azobisisobutyronitrile, azobisisoheptanenitrile, lauroyl peroxide, and dibenzoyl peroxide.

[0015] A preparation method of composite limestone powder concrete comprises the following steps: putting silicate cement, limestone powder, fly ash, coarse aggregate, fine aggregate, steel fiber and hollow glass microspheres into a mixing device, mixing and stirring at a rate of 150-250 r / min for 2-5 min; after the stirring is completed, adding the remaining raw materials, and continuing to stir at a rate of 350-500 r / min for 3-5 min; after the stirring is completed, pouring the obtained mixed slurry into a mold, and after solidification and natural curing for 28 days, high-strength crack-resistant concrete is obtained.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The invention uses methyl methacrylate, epoxy resin and triacetin as raw materials, adds octadecanoic acid and benzoic acid to the obtained reaction product after heat preservation and stirring reaction, stirs evenly and then heat preservation and stirring reaction is carried out, and finally a waterproofing agent is prepared through chemical reaction. The prepared waterproofing agent can be used as a raw material of concrete to effectively ensure the density of concrete, prevent external moisture from penetrating into the interior of concrete, and significantly improve the waterproof performance of concrete.

[0018] Furthermore, the present invention uses 2-methylacrylamide, maltose, 4-tert-butyl-1,2-dihydroxybenzene and trihydroxyethylamine as raw materials, and after heat preservation reaction, the resultant components are mixed and stirred evenly with methacrylic acid, methoxy polyethylene glycol monomethacrylate and a reaction accelerator, and a chemical reaction occurs between the relevant raw materials under the action of the reaction accelerator, and finally a functional additive is prepared. The prepared functional additive is used together with steel fiber as a raw material for concrete, which can not only effectively improve the mechanical properties of concrete, but also improve its crack resistance and durability.

[0019] In summary, the concrete prepared by the present invention not only has excellent mechanical properties and durability, but also has excellent waterproof performance, which ensures the quality of the concrete while also extending its service life to a certain extent. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] A composite limestone powder concrete is composed of the following raw materials in parts by weight: 320 parts of silicate cement, 1000 parts of coarse aggregate, 750 parts of fine aggregate, 80 parts of limestone powder, 60 parts of fly ash, 30 parts of steel fiber, 20 parts of hollow glass microspheres, 10 parts of waterproofing agent, 6 parts of functional additives and 200 parts of water.

[0023] The water content of limestone powder is less than 1.0wt%, and the specific surface area is 600m 2 / kg, 45μm sieve residue is less than 15wt%, average particle size is 7.5μm, and calcium carbonate content is greater than 75wt%.

[0024] The coarse aggregate is limestone crushed stone with a compressive strength greater than 90MPa, a needle-like content less than 5%, a mud content less than 1%, and a particle size of 5mm.

[0025] The fine aggregate is medium sand from Zone II, with an apparent density of 2650 kg / m 3 , particle diameter is 0.25mm, and mud content is less than 1.0%.

[0026] The diameter of the steel fiber is 0.2 mm, the length is 13 mm, and the aspect ratio is 65.

[0027] The bulk density of hollow glass microspheres is greater than 700kg / m 3 , the silicon dioxide content is greater than 50%, and the aluminum oxide content is greater than 20%.

[0028] The silicate cement used shall be P.O42.5 grade ordinary silicate cement; the fly ash used shall be F class II fly ash.

[0029] The preparation method of the waterproofing agent is as follows: methyl methacrylate, epoxy resin and triacetin are put into a reaction device at a mass ratio of 1:1.5:1, and mixed and stirred at a rate of 300r / min for 10min; then the obtained mixture is heated to 70°C, kept warm and stirred for reaction for 2h, and then 0.8 times the mass of octadecanoic acid and 1 times the mass of benzoic acid of methyl methacrylate are added, and after stirring evenly, the reaction is continued at a temperature of 70°C for 2h of keeping warm and stirring; after the reaction is completed, the resultant components are naturally cooled to room temperature to obtain the waterproofing agent.

[0030] The preparation method of the functional additive comprises the following steps: adding 2-methylacrylamide, maltose and water into a reaction kettle at a mass ratio of 1:0.8:3, adding 4-tert-butyl-1,2-dihydroxybenzene and 20% trihydroxyethylamine with a mass of 0.2% of 2-methylacrylamide respectively after sufficient stirring, mixing and stirring evenly, and then keeping the mixture warm at 50°C for 3 hours; after the reaction is completed, mixing and stirring the resultant components with 3 times the mass of methacrylic acid, 10 times the mass of methoxypolyethylene glycol monomethacrylate, and 0.02 times the mass of azobisisobutyronitrile respectively, and keeping the mixture warm at 65°C for 2 hours; after the reaction is completed, the functional additive is obtained.

[0031] A preparation method of composite limestone powder concrete comprises the following steps: putting silicate cement, limestone powder, fly ash, coarse aggregate, fine aggregate, steel fiber and hollow glass microspheres into a mixing device, mixing and stirring at a rate of 150 r / min for 2 minutes; after the stirring is completed, adding the remaining raw materials, and continuing to stir at a rate of 350 r / min for 3 minutes; after the stirring is completed, pouring the obtained mixed slurry into a mold, and after solidification and natural curing for 28 days, high-strength crack-resistant concrete is obtained.

[0032] Example 2

[0033] A composite limestone powder concrete is composed of the following raw materials in parts by weight: 350 parts of silicate cement, 1100 parts of coarse aggregate, 800 parts of fine aggregate, 100 parts of limestone powder, 80 parts of fly ash, 40 parts of steel fiber, 25 parts of hollow glass microspheres, 12 parts of waterproofing agent, 8 parts of functional additives and 210 parts of water.

[0034] The water content of limestone powder is less than 1.0wt%, and the specific surface area is 700m 2 / kg, 45μm sieve residue is less than 15wt%, average particle size is 7.5μm, and calcium carbonate content is greater than 75wt%.

[0035] The coarse aggregate is limestone crushed stone with a compressive strength greater than 90MPa, a needle-like content less than 5%, a mud content less than 1%, and a particle size of 5mm.

[0036] The fine aggregate is medium sand in zone II, with an apparent density of 2670 kg / m 3 , particle diameter is 0.4mm and mud content is less than 1.0%.

[0037] The diameter of the steel fiber is 0.2 mm, the length is 13 mm, and the aspect ratio is 65.

[0038] The bulk density of hollow glass microspheres is greater than 700kg / m 3 , the silicon dioxide content is greater than 50%, and the aluminum oxide content is greater than 20%.

[0039] The silicate cement used shall be P.O42.5 grade ordinary silicate cement; the fly ash used shall be F class II fly ash.

[0040] The preparation method of the waterproofing agent is as follows: methyl methacrylate, epoxy resin and triacetin are put into a reaction device at a mass ratio of 1:2:1.5, and mixed and stirred at a rate of 400r / min for 15min; then the obtained mixture is heated to 75°C, kept warm and stirred for reaction for 3h, and then 0.8 times the mass of octadecanoic acid and 1.2 times the mass of benzoic acid of methyl methacrylate are added, and after stirring evenly, the mixture is kept warm and stirred for reaction for 2h at a temperature of 75°C; after the reaction is completed, the resultant components are naturally cooled to room temperature to obtain the waterproofing agent.

[0041] The preparation method of the functional additive comprises the following steps: adding 2-methylacrylamide, maltose and water into a reaction kettle at a mass ratio of 1:1:4, adding 4-tert-butyl-1,2-dihydroxybenzene and 30% trihydroxyethylamine with a mass ratio of 0.3% of 2-methylacrylamide and stirring well, mixing and stirring evenly, and then keeping the mixture warm at 70°C for 4 hours; after the reaction is completed, mixing and stirring the resultant components with 3 times the mass of methacrylic acid, 10 times the mass of methoxypolyethylene glycol monomethacrylate and 0.03 times the mass of azobisisoheptonitrile, and keeping the mixture warm at 70°C for 3 hours; after the reaction is completed, the functional additive is obtained.

[0042] A preparation method of composite limestone powder concrete comprises the following steps: putting silicate cement, limestone powder, fly ash, coarse aggregate, fine aggregate, steel fiber and hollow glass microspheres into a mixing device, mixing and stirring at a rate of 200 r / min for 3 minutes; after the stirring is completed, adding the remaining raw materials, and continuing to stir at a rate of 400 r / min for 4 minutes; after the stirring is completed, pouring the obtained mixed slurry into a mold, and after solidification and natural curing for 28 days, high-strength crack-resistant concrete is obtained.

[0043] Example 3

[0044] A composite limestone powder concrete is composed of the following raw materials in parts by weight: 380 parts of silicate cement, 1200 parts of coarse aggregate, 850 parts of fine aggregate, 110 parts of limestone powder, 100 parts of fly ash, 50 parts of steel fiber, 30 parts of hollow glass microspheres, 15 parts of waterproofing agent, 10 parts of functional additives and 220 parts of water.

[0045] The water content of limestone powder is less than 1.0wt%, and the specific surface area is 750m 2 / kg, 45μm sieve residue is less than 15wt%, average particle size is 8.0μm, and calcium carbonate content is greater than 75wt%.

[0046] The coarse aggregate is limestone crushed stone with a compressive strength greater than 90MPa, a needle-like content less than 5%, a mud content less than 1%, and a particle size of 5mm.

[0047] The fine aggregate is medium sand in zone II, with an apparent density of 2670 kg / m 3 , particle diameter is 0.5mm and mud content is less than 1.0%.

[0048] The diameter of the steel fiber is 0.2 mm, the length is 13 mm, and the aspect ratio is 65.

[0049] The bulk density of hollow glass microspheres is greater than 700kg / m 3 , the silicon dioxide content is greater than 50%, and the aluminum oxide content is greater than 20%.

[0050] The silicate cement used shall be P.O42.5 grade ordinary silicate cement; the fly ash used shall be F class II fly ash.

[0051] The preparation method of the waterproofing agent is as follows: methyl methacrylate, epoxy resin and triacetin are put into a reaction device at a mass ratio of 1:2.5:2, and mixed and stirred at a rate of 500r / min for 20min; then the obtained mixture is heated to 80°C, kept warm and stirred for reaction for 3h, and then octadecanoic acid with a mass of 1.0 times that of methyl methacrylate and benzoic acid with a mass of 1.5 times that of methyl methacrylate are added, and after stirring evenly, the mixture is kept warm and stirred for reaction for 2-3h at a temperature of 80°C; after the reaction is completed, the resultant components are naturally cooled to room temperature to obtain the waterproofing agent.

[0052] The preparation method of the functional additive comprises the following steps: putting 2-methylacrylamide, maltose and water into a reaction kettle at a mass ratio of 1:1.2:5, adding 4-tert-butyl-1,2-dihydroxybenzene and 40% trihydroxyethylamine with a mass ratio of 0.5% of 2-methylacrylamide and stirring well, mixing and stirring evenly, and then keeping the mixture warm at 80°C for 5 hours; after the reaction is completed, mixing and stirring the resultant components with 4 times the mass of methacrylic acid, 15 times the mass of methoxy polyethylene glycol monomethacrylate and 0.04 times the mass of lauroyl peroxide, and keeping the mixture warm at 75°C for 5 hours; after the reaction is completed, the functional additive is obtained.

[0053] A preparation method of composite limestone powder concrete comprises the following steps: putting silicate cement, limestone powder, fly ash, coarse aggregate, fine aggregate, steel fiber and hollow glass microspheres into a mixing device, mixing and stirring at a rate of 250 r / min for 5 minutes; after the stirring is completed, adding the remaining raw materials, and continuing to stir at a rate of 500 r / min for 5 minutes; after the stirring is completed, pouring the obtained mixed slurry into a mold, and after solidification and natural curing for 28 days, high-strength crack-resistant concrete is obtained.

[0054] Comparative Example 1 is different from Example 1 in that an equal amount of triethanolamine is used to replace the waterproofing agent in this comparative example.

[0055] Comparative Example 2 is different from Example 1 in that an equal amount of sodium lignin sulfonate is used to replace the functional additive in this comparative example.

[0056] Performance test: The relevant properties of the composite limestone powder concrete samples provided in Examples 1 to 3 and Comparative Examples 1 to 2 were tested respectively, and the test data obtained were recorded in the following table:

[0057]

[0058] By comparing and analyzing the relevant data in the table, it can be seen that the composite limestone powder concrete prepared by the present invention not only has excellent mechanical properties and durability, but also has excellent waterproof performance, which ensures the quality of concrete and also prolongs its service life to a certain extent. This shows that the composite limestone powder concrete and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0059] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0060] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A composite limestone powder concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 320-380 parts of silicate cement, 1000-1200 parts of coarse aggregate, 750-850 parts of fine aggregate, 80-110 parts of limestone powder, 60-100 parts of fly ash, 30-50 parts of steel fiber, 20-30 parts of hollow glass microspheres, 10-15 parts of waterproofing agent, 6-10 parts of functional additives and 200-220 parts of water.

2. The composite limestone powder concrete according to claim 1, characterized in that: The water content of the limestone powder is less than 1.0wt%, and the specific surface area is 600-750m 2 / kg, 45μm sieve residue is less than 15wt%, average particle size is 7.5-8.0μm, and calcium carbonate content is greater than 75wt%.

3. The composite limestone powder concrete according to claim 1, characterized in that: The coarse aggregate is limestone crushed stone with a compressive strength greater than 90 MPa, a needle-like content less than 5%, a mud content less than 1%, and a particle size of 5 to 25 mm.

4. The composite limestone powder concrete according to claim 1, characterized in that: The fine aggregate is medium sand from zone II, and its apparent density is 2650-2670 kg / m 3 The particle diameter is 0.25-0.5 mm and the mud content is less than 1.0%.

5. The composite limestone powder concrete according to claim 1, characterized in that: The bulk density of the hollow glass microspheres is greater than 700 kg / m 3 , the silicon dioxide content is greater than 50%, and the aluminum oxide content is greater than 20%.

6. The composite limestone powder concrete according to claim 1, characterized in that: The silicate cement is selected from P.O42.5 grade ordinary silicate cement; the fly ash is selected from F class II fly ash.

7. The composite limestone powder concrete according to claim 1, characterized in that: The preparation method of the waterproofing agent is as follows: methyl methacrylate, epoxy resin and triacetin are put into a reaction device at a mass ratio of 1:1.5-2.5:1-2, and mixed and stirred at a rate of 300-500r / min for 10-20min; then the obtained mixture is heated to 70-80°C, kept warm and stirred for reaction for 2-3h, and then 0.8-1.0 times the mass of octadecanoic acid and 1-1.5 times the mass of benzoic acid are added, and after stirring evenly, the mixture is kept warm and stirred for reaction for 2-3h at a temperature of 70-80°C; after the reaction is completed, the resultant components are naturally cooled to room temperature to obtain the waterproofing agent.

8. The composite limestone powder concrete according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: adding 2-methyl acrylamide, maltose and water into a reaction kettle at a mass ratio of 1:0.8-1.2:3-5, adding 4-tert-butyl-1,2-dihydroxybenzene with a mass ratio of 0.2-0.5% of 2-methyl acrylamide and 20-40% of trihydroxyethylamine after sufficient stirring, mixing and stirring evenly, and then keeping the mixture warm at a temperature of 50-80°C for reaction for 3-5 hours; after the reaction is completed, mixing and stirring the resultant components with 3-4 times the mass of methacrylic acid, 10-15 times the mass of methoxy polyethylene glycol monomethacrylate, and 0.02-0.04 times the mass of the reaction accelerator, and keeping the mixture warm at a temperature of 65-75°C for reaction for 2-5 hours; after the reaction is completed, the functional additive is obtained.

9. The composite limestone powder concrete according to claim 8, characterized in that: The reaction accelerator is selected from any one of azobisisobutyronitrile, azobisisoheptanenitrile, lauroyl peroxide and dibenzoyl peroxide.

10. A method for preparing composite limestone powder concrete according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: putting silicate cement, limestone powder, fly ash, coarse aggregate, fine aggregate, steel fiber and hollow glass microspheres into a mixing device, mixing and stirring at a rate of 150-250 r / min for 2-5 minutes; after the stirring is completed, adding the remaining raw materials, and continuing to stir at a rate of 350-500 r / min for 3-5 minutes; after the stirring is completed, pouring the obtained mixed slurry into a mold, and after solidification and natural curing for 28 days, high-strength crack-resistant concrete is obtained.

Citation Information

Patent Citations

  • A green concrete with high limestone powder content

    CN108249849B

  • Modified limestone powder for manufacturing concrete

    CN113603382A

  • Durable concrete and preparation method thereof

    CN116639938A